2010
DOI: 10.1007/s00003-010-0595-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sugar and saponin contents and sensory attributes of white asparagus

Abstract: Sweetness and bitterness can be regarded as mediators of vegetable preferences and intake, thus playing a prominent role in quality assessment. Sugars and saponins are known to cause sweet and bitter perception in asparagus. In the present investigation a trained, quantitative-descriptive sensory panel was used to assess various asparagus cultivars with known contents of sugars and saponins. Therefore, six asparagus cultivars, representing the range of cultivars used in commercial white asparagus production in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
(18 reference statements)
3
13
0
Order By: Relevance
“…Sugar composition in the spears showed similar results to other former studies, consisting 50 54% of fructose, 42 44% of glucose and 4 5% sucrose (Matsubara, 1981;Shou et al, 2007;Brueckner et al, 2010), and there was no significant difference among experimental plot observed. So, it is clear that there was no negative impact of supplemental lighting on sugar.…”
Section: Discussionsupporting
confidence: 88%
“…Sugar composition in the spears showed similar results to other former studies, consisting 50 54% of fructose, 42 44% of glucose and 4 5% sucrose (Matsubara, 1981;Shou et al, 2007;Brueckner et al, 2010), and there was no significant difference among experimental plot observed. So, it is clear that there was no negative impact of supplemental lighting on sugar.…”
Section: Discussionsupporting
confidence: 88%
“…Although excessive bitterness decreases palatability, some consumers still prefer a degree of bitterness in asparagus. Protodioscin, a furostanol saponin compound, was confirmed as the principal saponin compound in white asparagus spears (Brueckner et al, 2010;Chin et al, 2002;Lee et al, 2010;Maeda et al, 2012;Schwarzbach et al, 2006;Shao et al, 1996;Wang et al, 2003). In a previous study, we found that blanching methods influenced the protodioscin content, but did not affect the sugar content .…”
Section: Introductionmentioning
confidence: 73%
“…Quantification method for protodioscin using HPLC equipped with an ELSD For the purpose of quantifying protodioscin content in asparagus, high performance thin layer chromatography (HPTLC) or HPLC equipped with a mass spectrometer (LC-MS) has been utilized (Brueckner et al, 2010;Maeda et al, 2012;Schwarzbach et al, 2006;Wang et al, 2003); however, both methods have disadvantages such as labor intensiveness, variability, low sensitivity (HPTLC), and relatively high initial and operational costs (LC-MS). Recently, a novel method using HPLC equipped with a UV detector was reported by Lee et al (2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory qualities can be regarded as mediators of food preferences and intake, thus playing a prominent role in quality assessment (Brueckner et al 2010). Sensory evaluation can provide important and useful information to the food industry and food scientists about the sensory characteristics of food (Debjani et al 2011).…”
Section: Introductionmentioning
confidence: 99%